PDE3 inhibition in dilated cardiomyopathy - Movsesian, Matthew (2011)
In dilated cardiomyopathy, a condition characterized by chamber enlargement and reduced myocardial contractility, decreases in β-adrenergic receptor density and increases in Gαi and β-adrenergic receptor kinase activities attenuate the stimulation of adenylyl cyclase in response to catecholamines. PDE3 inhibitors have been used to ‘overcome’ the reduction in cAMP generation by blocking cAMP hydrolysis. These drugs increase contractility in the short-term, but long-term administration leads to an increase in mortality that correlates with an increase in sudden cardiac death. Whether separate mechanisms account for these beneficial and harmful effects, and, if so, whether PDE3 can be targeted so as to increase contractility without increasing mortality are questions that remain unanswered.